The Role of Halal Certification as A State Regulatory Instrument in Strengthening the Competitiveness of Sharia-Based Msmes in The Global Market - Abdul Basit (Lembaga Bale Literasi, 2026)
This study aims to analyze the role of halal certification as a state regulatory instrument in strengthening the competitiveness of sharia-based MSMEs in the global market. The focus of the study covers the role of halal certification as a state regulatory instrument. The method used in this study is a systematic literature review approach to identify, evaluate, and interpret all relevant studies related to halal certification, state regulatory instruments, and globalization in the halal industry. The results of the analysis show that the role of the state is not only limited to issuing halal certification regulations, but also includes strengthening the halal ecosystem as a whole. Support in the form of policy dissemination, certification cost subsidies, assistance for MSMEs, and synergy with Islamic financial institutions has been proven to contribute to accelerating the halal certification process and increasing the readiness of MSMEs to face global competition